Employability, organizational commitment and person-organization fit among nurses in China: A correctional cross‐sectional research - Wei Yan; Xingqu Wu; Huan Wang; Yaling Zhang; Lixia Cheng; Xinyao Zhou; Huan Chen; Caiping Song; Junying Ye (Wiley, 2023)
Abstract Aim This study aimed to explore the effect of training on organizational commitment, the mediating effect of employability and the moderating role of person-organization fit. Design A correctional cross‐sectional research design was adopted for this study. Methods A questionnaire‐based survey of 859 nurses in a public hospital in Western China was conducted to identify their perceptions of training, employability, organizational commitment and person-organization fit. Hierarchical linear regression and conditional process analysis on moderated mediation were performed. Results Training had a positive effect on organizational commitment (p < .01). Internal and external employability mediated the relationship between training and organizational commitment (p < .01). Person-organization fit enhanced the indirect effect of training on organizational commitment through external employability (p < .05).